The Role of Financial Management in Testing Environmental Kuznets Curve in Kuwait: Evidence from ARDL Bound Testing Approach - Al-Hussaini, Ahmed Nahar (International Journal of Energy Economics and Policy, 2019)
The aim of the current investigates the relationship of energy utilization and financial management & expansion in influencing environmental degradation of Kuwait. The current study used time series data from 1981 to 2017. The results of ARDL bound testing confirm that economic growth, square of economic growth, energy consumption and financial management are the valid determinants of environmental degradation in Kuwait. Moreover, the results attest that financial management have a positive outcome on environmental degradation in Kuwait which suggests that the financial management is one of the main sources of increasing environmental degradation in Kuwait over the long run. Likewise, it tends to be discussed that all components including economic growth, energy consumption and financial management assume a noteworthy contributor to worsening the environmental condition in Kuwait and confirm the EKC in Kuwait. The empirical findings of the examination help the policy makers in identification and the awareness regarding the specific link of power consumption with rising ecological adversity in Kuwait. Also, our study elaborates the policy makers in capturing the efficiency of financial management in addressing the critical issue of rising carbon-di-oxide emission in the country. Keywords: Financial Management, Energy Consumption, Environmental Kuznets Curve, Kuwait JEL Classifications: G2, Q5, Q43 DOI: https://doi.org/10.32479/ijeep.7753